Spatial and temporal variability in the chemical properties of the oxic and suboxic layers of the Black Sea - Tuğrul, Süleyman; Murray, James W.; Friederich, Gernot E.; Salihoğlu, İlkay (Journal of marine systems, 2014)
The Black Sea, a land-locked deep basin with sulfide bearing waters below 150–200m, has been subject to anthropogenic pressures since the 1970s. Large inputs of nutrients (nitrate — N, phosphate — P, silicate — Si) with high N/P but low Si/N ratios and subsequent development of intensive eutrophication over the basin have changed vertical distributions and inventories of nutrients and redox-sensitive metals in the oxic, suboxic and anoxic layers. Chemical data sets obtained between 1988 and 2010, and older data from before 1970 were evaluated to assess spatial/temporal variations of the dissolved oxygen (O2), nutrients and dissolved/particulate manganese (Mnd, Mnp) in the water column from the lower salinity, oxygenated surface waters through the SubOxic Layer (SOL; O2<20μM; H2S<1μM) to the anoxic, sulfidic water interface. Correlations were observed between salinity and nutrients (nitrate, silicate) in the nearshore waters off the Danube delta and in the southwestern (SW) coastal waters which had low Si/N ratios. Surface waters from the western central gyre were consistently depleted in nitrate and phosphate with low N/P but higher Si/N molar ratios throughout the year. Chemical profiles obtained recently in the Rim Current and western central gyre displayed very similar vertical features through the halocline to the sulfidic water interface. However, in the SW coastal margin, lateral intrusion of O2 and nutrients by the Bosporus Plume resulted in formation of secondary maxima of nitrate, nitrite and O2 in the SOL, and local deepening of the first appearance of anoxic, sulfidic waters. Before the mid 1960s, nitrate-enriched major rivers fed the Black Sea with high N/P ratios (>50). The surface waters over the basin were rich in silicate (25–70μM), but poor in nitrate (<0.1μM) and phosphate (0.05–0.3μM), resulting in very high Si/N (>500) but very low N/P (<1.0) ratios. After the mid 1970s, construction of dams, especially on the Danube River, resulted in lower Si concentrations. At this time the increased loads of anthropogenic nitrate and phosphate by the major rivers resulted in lower Si/N, but still high N/P molar ratios, which enhanced eutrophication (production of particulate organic matter, POM) drastically in the coastal waters. This led to reductions in the surface Si/N ratio by up to 500-fold in the western basin while the N/P ratio increased. The enhanced POM export increased the nitrate inventory and thus N/P ratios of the NW shelf waters spreading over the whole basin. The increased export of POM decreased the Si inventory of the upper layer down to the boundary of sulfidic waters. This export also increased O2 consumption and removal of nitrate to N2 form by denitrification in the oxic/suboxic interface, leading to seasonal/decadal changes in the boundaries of the nitracline and main oxycline and changes in the slopes of the nitrate-phosphate and Apparent Oxygen Utilization (AOU)-nitrate regressions in the steep oxycline down to the SOL. These slopes are much smaller than those observed in the lower layer of Marmara Sea fed by the Black Sea outflow. The enlargement of SOL by ~15–20m after the 1970s modified the vertical features of nitrate, phosphate and manganese (Mnd, Mnp) species in the redox gradient zone. •Spatial/temporal changes of the Black Sea chemistry were investigated.•Important drivers were nutrient inputs from the Danube and export of POM to the SOL.•After the 1970s, nutrient inventories and Si/N/P ratios changed in the oxic and suboxic layers.•After the 1970s, the SOL, nitrate maximum and the phosphate minimum became more coherent.•Lateral intrusions from the Bosporus Plume modify the major chemical features of SOL.